2017
DOI: 10.4236/oalib.1103711
|View full text |Cite
|
Sign up to set email alerts
|

Does Mobile Phone Radiation Affect Sperm Quality?

Abstract: Background: Male infertility represents almost half of all infertility cases worldwide. High social activities have made some men use earphones or hands-free devices to stay in touch while on the move; hence, often giving radiation exposure to male reproductive organs when their mobile phone is kept in trousers' pocket or on the belt. Because testis is an organ that is susceptible to radiation, the effect of radiation on testis is worth investigating. Objective: This study aimed to determine the direct effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the investigations are contradictory. Some studies have shown negative effects on sperm motility but not on sperm count (Fejes et al, 2005), but others have found no link between sperm quality and exposure to electromagnetic radiation (Feijo et al, 2011 andSyam et al, 2017). Another study ZANCO Journal of Pure and Applied Sciences 2022 discovered harmful effects on sperm viability and motility from use of the mobile phones (Adams et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the investigations are contradictory. Some studies have shown negative effects on sperm motility but not on sperm count (Fejes et al, 2005), but others have found no link between sperm quality and exposure to electromagnetic radiation (Feijo et al, 2011 andSyam et al, 2017). Another study ZANCO Journal of Pure and Applied Sciences 2022 discovered harmful effects on sperm viability and motility from use of the mobile phones (Adams et al, 2014).…”
Section: Introductionmentioning
confidence: 99%